1987
DOI: 10.1128/jcm.25.11.2085-2089.1987
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity test for Listeria monocytogenes using immunocompromised mice

Abstract: The lethality of Listeria isolates was determined with normal adult mice and mice that were immunocompromised by treatment with 20 mg of carrageenan per kg. The mean 50% lethal doses (LD50s) of the pathogenic isolates were significantly lower (a = 0.05) in' the immunocompromised mice than in the untreated mice, with an average reduction of 5.8 1glo units. Ini contrast, the mean LD50s of the nonpathogenic isolates were lowèr in the immunocompromised mice by an average of only 0.4 loglo unit, a differehce that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 37 publications
4
30
1
Order By: Relevance
“…The mouse bioassay has proved to be an extremely sensitive assay for assessing the pathogenicity of L. monocytogenes. Experiments carried out by Mainou-Fowler et al [11] and Stelma et al [12] demonstrated that virulence of L. monocytogenes for man can be correlated with pathogenicity in mice. In the experiments presented here three strains were discovered, belonging to serotypes 3a and 4a, that showed intermediate levels of replication in target organs of infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse bioassay has proved to be an extremely sensitive assay for assessing the pathogenicity of L. monocytogenes. Experiments carried out by Mainou-Fowler et al [11] and Stelma et al [12] demonstrated that virulence of L. monocytogenes for man can be correlated with pathogenicity in mice. In the experiments presented here three strains were discovered, belonging to serotypes 3a and 4a, that showed intermediate levels of replication in target organs of infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…seeligeri also produce hemolysins, but these species have rarely been encountered in human infections. Stelma et al ( 1987) concluded from studies in an immunocompromised mouse model that neither of these species is pathogenic. In contrast, Farber and Speirs (1987) found that a hemolytic strain of L .…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenicity testing of Listeria spp. has often been performed by using the FDA approved mouse model (Stelma et al 1987); however, this is not feasible for routine use. As a substitute, use of various tissue culture cell lines have been proposed by several researchers to test the cytopathogenicity of Listeria spp.…”
Section: Introductionmentioning
confidence: 99%